The Sense of Place in Community Participation Through Tactical Urbanism in Bundaran HI, Jakarta - Alyani, Salsabila Andara Siskania; Herlily, Herlily (UI Scholars Hub, 2019)
Sense of place is a concept within urban design. In the realm of formal city planning, sense of place is likely correlated with physical feature of a city. However, academic studies shows that sense of place is multidimensional, which involves factors that is beyond mere physical attributes. In the other hand, tactical urbanism as an emerging concept which describes intervention that is implemented in a city, is conceived as public’s opportunistic response to formal spatial planning. Being associated as interventions throughout the city, one of tactical urbanism’s main character is its bottom-up nature which responds certain issues that lie behind the movement. Moreover, tactical urbanism focuses on action. In Indonesia, negotiation of micro-scale spaces such as pedestrian, street corners, and hawker spaces can be considered as tactical urbanism action, as it defines the character of an area which eventually generates certain sense of place. The focus of this study is to investigate the creation of sense of place within a public realm that undergoes tactical urbanism initiation by interrogating whether the factors of tactical urbanism contribute to enhancement of a certain area’s sense of place. We will use emic approach to understand the tactical urbanism adaptation. The analysis will show how certain adaptation of tactical urbanism is implemented in the given case study. By examining the tactical urbanism process, this paper shows the role of actors and their contribution in the creation of sense of place.